Uma arquitetura para controle de privacidade na web - Lucila Ishitani (2003)
This thesis proposes an architecture that allows users to enhance their privacy control over the computational environment. Web privacy is a topic that is raising, nowadays, many discussions. Firstly because many people do not know how their privacy can be violated or what can be done to protect it. In general, people do not even know what privacy means, and there is an overlap of the concepts of privacy and security, that needsto be cleared. Another topic to be discussed is the value that each one gives to privacy and when it is worth to give up some privacy in order to profit from several different Web services. The value of privacy has generated many conflicts. Among them, we would like to show up the one that happens between privacy and personalization: by one side, usersappreciate the idea of receiving personalized services and do not pprove the collection, tracing and analysis of their actions; by the other side, personalization services need this type of information in order to profile their users. The architecture proposed in this thesis helps users to understand better how their privacy can be invaded and, at the same time, gives them a better control of their privacy, through anonymity, without preventing them from receiving personalized services. This thesis also includes a conceptual vision of Web privacy: concepts and importance of privacy; a distinction between privacy and security; Web privacy protection.